The Sibawayhi foundation and the subsequent pragmatic-linguistic approach in modern linguistic studies - lemounes, khayreddine (El Omda in Linguistics and Discourse Analysis, 2025)
There is no doubt that the ancient Arab linguists have elaborated on most aspects of linguistics, and this indicates their comprehension of all levels of language. This has generated a tremendous cognitive momentum for these innovators - headed by the imam of grammarians and the wonder of the age, Sibawayh - and the contemporary intellectual arena in linguistic studies has witnessed the emergence of several diverse critical trends and approaches, such as the structural, transformational, generative, and stylistic approaches, among others…However, these approaches have always dealt with the linguistic phenomenon from specific perspectives that neglect many important aspects, and they continued in this manner for a long time, until pragmatics .